1972
DOI: 10.1182/blood.v40.3.333.333
|View full text |Cite
|
Sign up to set email alerts
|

Present Status of Spiculed Red Cells and Their Relationship to the Discocyte-Echinocyte Transformation: A Critical Review

Abstract: The literature on spiculed red cells, contains a redundant nomenclature and contradictory claims on the pathogenesis of the abnormal red cells. A resolution of these difficulties requires knowledge of the many conditions that induce crenation in normal and abnormal red cells because these artifacts have frequently been confused with spiculed cells in the patient’s circulation. The biconcave red cells (disocytes) can be transformed into crenated red cells (echinocytes) (1) by extrinsic factors (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
1

Year Published

1976
1976
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(64 citation statements)
references
References 24 publications
4
59
0
1
Order By: Relevance
“…Different studies have suggested that morphological changes in erythrocytes are possibly due to oxidative stress induced by administration of pesticides [28,[36][37][38]. It has also been reported that changes in the membrane lipid composition might lead to morphological changes in blood cells in response to administration of various pesticides [39,40]. Diplock et al [41] have suggested that vitamin E is responsible for structurally stabilizing biomembranes due to the physico-chemical interactions between α-tochopherol and unsaturated fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have suggested that morphological changes in erythrocytes are possibly due to oxidative stress induced by administration of pesticides [28,[36][37][38]. It has also been reported that changes in the membrane lipid composition might lead to morphological changes in blood cells in response to administration of various pesticides [39,40]. Diplock et al [41] have suggested that vitamin E is responsible for structurally stabilizing biomembranes due to the physico-chemical interactions between α-tochopherol and unsaturated fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…To the first type belong uraemic patients fed parenterally in whom severe hypophosphataemia developed (Lichtman et al, 1969;Jacob & Amsden, 197I), patients with congenital deficiency of pyruvate kinase (Oski et al, 1964) or patients with phosphoglycerate kinase deficiency. To the second type belong rare cases of heparinized patients on cardiac by-pass in whom fatty acids presumably accumulate in the plasma from which they are normally cleared instantaneously (Brecher & Bessis, 1972). Recently, Harlan et al (1976) described up to 90% of echinocytes in patients with extensive burns and implicated abnormally low phospholipids as the cause, although the exact mechanism has not been definitely established.…”
Section: Discussionmentioning
confidence: 99%
“…Morphology of 80 resting RBCs was studied on video recordings for each sample at each lipid A concentration. Since echinocytes and spherocytes were the predominant shape changes, we used the criteria established by Brecher et al [17] for the characterization of discocytes, echinocytes (stage 1-3) and spheroechinocytes.…”
Section: Rbc Morphologymentioning
confidence: 99%